Earwig-inspired foldable origami wing for micro air vehicle gliding - Ishiguro, Risa; Kawasetsu, Takumi; Motoori, Yutaro; Paik, Jamie; Hosoda, Koh (Frontiers in Robotics and AI, 2023)
Foldable wings serve as an effective solution for reducing the size of micro air vehicles (MAVs) during non-flight phases, without compromising the gliding capacity provided by the wing area.Among insects, earwigs exhibit the highest folding ratio in their wings. Inspired by the intricate folding mechanism in earwig hindwings, we aimed to develop artificial wings with similar highfolding ratios. By leveraging an origami hinge, which is a compliant mechanism, we successfully designed and prototyped wings capable of opening and folding in the wind, which helps reduce the surface area by a factor of seven. The experimental evaluation involved measuring the lift force generated by the wings under Reynolds numbers less than 2.2 × 10 5 . When in the open position, our foldable wings demonstrated increased lift force proportional to higher wind speeds.Properties such as wind responsiveness, efficient folding ratios, and practical feasibility highlight the potential of these wings for diverse applications in MAVs.